2013
DOI: 10.3389/fnsys.2013.00030
|View full text |Cite
|
Sign up to set email alerts
|

A novel tool for evaluating children's musical abilities across age and culture

Abstract: The present study introduces a novel tool for assessing musical abilities in children: The Montreal Battery of Evaluation of Musical Abilities (MBEMA). The battery, which comprises tests of memory, scale, contour, interval, and rhythm, was administered to 245 children in Montreal and 91 in Beijing (Experiment 1), and an abbreviated version was administered to an additional 85 children in Montreal (in less than 20 min; Experiment 2). All children were 6–8 years of age. Their performance indicated that both vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 55 publications
(64 reference statements)
1
91
2
Order By: Relevance
“…Even in this very large sample size including a range of ages, there was no evidence that the m-factor was correlated with age. This contrasts with Peretz et al (2013), who found a small correlation between the Montreal Battery of Evaluation of Musical Abilities (MBEMA) with age (Pearson's r varying from 0.29 for untrained children to 0.31 for musically trained children) in a population from 6 to 8 years old). Regarding our lack of correlation with age, it is important to emphasize that this is a cross-sectional study.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…Even in this very large sample size including a range of ages, there was no evidence that the m-factor was correlated with age. This contrasts with Peretz et al (2013), who found a small correlation between the Montreal Battery of Evaluation of Musical Abilities (MBEMA) with age (Pearson's r varying from 0.29 for untrained children to 0.31 for musically trained children) in a population from 6 to 8 years old). Regarding our lack of correlation with age, it is important to emphasize that this is a cross-sectional study.…”
Section: Discussioncontrasting
confidence: 62%
“…Thus, the items are stable indicators of MP. Previously, different hypotheses have been raised in terms of comparing cultures on their MP skills (Zatorre, 2016) and language background (Peretz et al, 2013). However, without precise information regarding batteries designed to measure MP and their invariance features in those target groups, results may be biased due to differential item functioning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations